Evaluation of Efficiency and Carbon Emissions of Fresh Fruit Bunches (FFB) Transportation by Company and Contractor Dump Trucks in a Low Carbon Development Framework - Aksyani, Ferdi Fiki; Purboseno, Sentot; Yomo, Seno Ajar (ARRUS Journal of Engineering and Technology, 2025)
This study aims to evaluate the efficiency of transporting Fresh Fruit Bunches (FFB) from the Harvesting Point (TPH) to the Palm Oil Mill (PKS) using a fleet of company-owned and contractor-owned dump trucks at PT Persada Sejahtera Agro Makmur. Parameters analyzed included travel time, load capacity, fuel consumption, operational costs, and estimated carbon emissions using the IPCC 2019 approach. The results show that the company's dump trucks have shorter travel times, larger load capacities, lower fuel consumption, and lower hourly operating costs than the contractor's dump trucks. Annual carbon emissions from the company's dump trucks are 27,389 kg CO₂, while the contractor's dump trucks produce 29,346 kg CO₂. Simulations of converting to B50 biodiesel and electric vehicles indicate potential energy cost savings of up to IDR 1.47 billion and emission reductions of up to 1,013 tons of CO₂ over five years. This research supports the development of a low-carbon logistics system in the palm oil plantation sector